On the role of different annealing heat treatments on mechanical properties and microstructure of selective laser melted and conventional wrought Ti-6Al-4V. Issue 2 (20th March 2017) - Khorasani, AmirMahyar; Gibson, Ian; Goldberg, Moshe; Littlefair, Guy
Abstract : Purpose: The purpose of this study was to conduct various heat treatments (HT) such as stress relief annealing, mill annealing, recrystallization (α + β) annealing and β annealing followed by furnace cooling (FC) that were implemented to determine the effect of these on mechanical properties and the microstructure of selective laser melted and wrought samples. The mentioned annealings have been carried out to achieve the related standards in the fabrication of surgery implants. Design/methodology/approach: In this paper, based on F2924-14 ASTM standard SLM and conventionally wrought parts were prepared. Then HT was performed and different characteristics such as microstructure, mechanical properties, macro-hardness and fracture surface for selective laser melted and wrought parts were analysed. Findings: The results show that the high cooling rate in selective laser melting (SLM) generates finer grains. Therefore, tensile strength and hardness increase along with a reduction in ductility was noticed. Recrystallization annealing appears to give the best combination of ductility, strength and hardness for selective laser melted parts, whilst for equivalent wrought samples, increasing HT temperature results in reduction of mechanical properties. Originality/value: The contributions of this paper are discussing the effect of different annealing on mechanical properties and microstructural evolution based on new ASTM standards for selective laser melted samples and comparing them with wrought parts.